Doubling farmer’s income through agroforestry: A policy perspective - Singh, Mahendra; Sridhar, K.B.; Kumar, Dhiraj; Utthappa, A.R.; Dwivedi, R.P.; Dev, Inder; Rizwi, R.H.; Tewari, R.K.; Chaturvedi, O.P. (Indian Journal of Agroforestry, 2020)
The study examines the viability of agroforestry to enhance farmers’ income with the support of various concerned policy measures. The field survey was conducted in Yamunanagar district of Haryana. To calculate the time value of money, 12% of discount rate was considered. Results verified the financial viability and profitability of agroforestry with existing prominent crop rotations in Indo-Gangetic plain. The trend in price of poplar showed the volatility situation and the price of all categories of poplar declined to one-third during last three years. The situation of import and rate of change in custom duty on wood based products are also presented, which verified the policy fatigued on agroforestry in the country. The study suggests that net income of farmers from existing rice-wheat system (`327703/ha) can be doubled through agroforestry system (` 594811/ha) and may be even tripled (` 898537/ha) if the value of carbon sequestered is considered within seven years of short span. The volatility in price of wood negatively impacted the agroforestry farmer’s income and there is situation of market failure and urgent need for identification of factors responsible and government interventions. The price stabilization of wood is a necessary condition for enhancement of farmer’s income. There is an urgent need of synergistic policy interactions between agroforestry and other related sectors such as policy for wood, trade, credit, subsidy, energy and forest, which substantially affect the development of agroforestry. A significant research effort is thus, indispensable both for generating information and developing an appropriate analytical framework to assess the impact of various sectoral policies on development of agroforestry and farmer’s income.